PEMBELAJARAN KALAM BERBASIS PHONETIC ACCURACY UNTUK MENINGKATKAN KEMAMPUAN BERBICARA BAHASA ARAB - Kholisin Kholisin (Fakultas Sastra Universitas Negeri Malang, 2015)
This study aims to develop the the teaching and learning model of kalam (conversation) based on phonetic accuracy to improve students’ ability in speaking Arabic. The research was conducted through questionnaires, interviews, error analysis, and content analysis. The results of the study described as follows. There are two forms of phonetic errors in student’s pronunciation, namely the segmental and supra-segmental errors; most of the teachers and students did not care to the phonetic errors on students speech; however, most of them consider that it is important to have a special emphasis on the phonetic element in learning kalam; the teaching material subjects of kalam used all this time did not emphasize specifically on phonetic accuracy; and the teachers and students suggested that the textbook of kalam be completed with special training of phonetic accuracy and be done early. Based on these results, the teaching and learning models of kalam need to be designed